Distance decay effects predominantly shape spider but not carabid community composition in crop fields in north-western Europe - Mei, Zulin; Scheper, Jeroen; Bommarco, Riccardo; de Groot, Gerard Arjen; Garratt, Michael P.D.; Potts, Simon G.; Redlich, Sarah; Smith, Henrik G.; van der Putten, Wim H.; van Gils, Stijn; Kleijn, David (Basic and applied ecology, 2024)
Agricultural intensification and expansion are regarded as main drivers of biodiversity loss. This conclusion is mainly based on observed declines of local diversity (α-diversity), while effects on community composition homogenization (decrease of β-diversity) at a larger spatial scale are less well understood. Carabid beetles and spiders represent two widespread guilds and are important predators of pest species. Here we surveyed carabid beetles and spiders in 66 winter wheat fields in four northwestern European countries (Germany, the Netherlands, Sweden and UK) and analyzed how their community composition was related to geographic distance (separation distance between any pairwise fields) and three environmental variables: crop yield (proxy for land-use intensity), percentage cropland (proxy for landscape complexity) and soil organic carbon content (proxy for local soil conditions). We further analyzed whether the relationship between carabid beetle and spider community composition and geographic distance was influenced by environmental variables. We found that, 55 % and 75 % of all observed carabid and spider individuals, respectively, belonged to species that occurred in all four countries. However, individuals of species that were unique to a particular country only accounted for 3 % of all collected individuals for both taxa. Furthermore, we found a negative relationship between distance and similarity of spider communities but not for carabid beetle communities. None of the environmental variables were related to similarity of carabid beetle and spider communities, nor moderated the effects of distance. Our study indicates that across a great part of the European continent, arthropod communities (especially carabid beetles) in agricultural landscapes are composed of very similar species that are robust to current variations in environment and land-use.